Photosynthetic activity and yield of pegaga (Hydrocotyle bonariensis) grown under natural and artificial light / Indiran Nair Narayanan - Indiran Nair , Narayanan (2020)
Large leaf pennywort (Hydrocotyle bonariensis) also known as Pegaga in Malaysia, is an herb belonging to the family Araliaceae and commonly used as a culinary leafy vegetable and in preparation of traditional medicines to treat various symptoms of ophthalmic diseases and eczema. The plant is also used as an emetic, diuretic and laxative. With the increasing demand for H. bonariensis by the herbal industry, sourcing plant materials from natural habitats is no longer an economically viable or environmentally sustainable proposition. H. bonariensis is highly sensitive to direct sunlight exposure and water scarcity, which makes successful farming dependent on weather conditions and cultivation practices. Thus, indoor cultivation with optimized lighting system, pertinent water and nutritional supply will be ideal for large-scale production of H. bonariensis. Light-emitting diodes (LEDs) have emerged as one of the promising artificial lighting systems for the plant growth. LED offer technical advantages over traditional lighting sources such as high flexibility for customizing the light spectrum, lower thermal radiation emission, lower energy requirement and high safety performance. In this study, we investigated the influence of LED lighting on growth and photosynthesis of H. bonariensis. Three experimental LED lighting systems, a) Blue and Red (B+R), b) Blue, Red and Green (B+R+G), and c) Blue, Red and Ultraviolet (B+R+U) were compared with natural daylight (NL) for H. bonariensis growth and photosynthesis (20 biological replicates x 3 experimental replicates = 60 plants). Results showed plants grown under the B+R lighting system for a period of 50 days to have higher fresh and dry biomass (fresh biomass; 1180.04 ± 0.085 mg, dry biomass; 190.86 ± 0.002 mg) compared to B+R+G (fresh biomass; 665.84 ± 0.030 mg, dry biomass; 156.56 ± 0.004 mg), B+R+U (fresh biomass; 403.00 ± 0.002 mg, dry biomass; 120.50 ± 0.011 mg) and NL (fresh biomass; 436.00 ± 0.003 mg, dry biomass; 110.84 ± 0.007 mg). Furthermore, photosynthetic pigment content (Chl-a; 17.91 ± 0.14 μg/ml, Chl-b; 8.33 ± 0.19 μg/ml, carotenoids; 3.72 ± 0.38 μg/ml) in plants grown under the B+R lighting system was found to be much higher compared to that of plants grown under the other LED lighting combinations and under NL. The higher photosynthetic pigment and biomass followed by large leaf area (5.61 ± 0.04 cm2), greater plant height (5.87 ± 0.638 cm), and higher number of leaves (17.50 ± 0.761) for plants grown under the B+R LED lighting system indicates that B+R lighting is the most suitable of the systems tested for efficient H. bonariensis farming.